Adsorption of Heavy Metal Mercury (Hg) Using Meranti Wood as Activated Carbon - Zimon Pereiz; Chuchita Chuchita; Efriyana Oksal; Miranti Maya Sylvani; Yunus Pebriyanto; Oktaviani Naulita Turnip; Ahmad Irawan (Jurnal Kimia Fullerene, 2025)
The objective of this research is to assess the adsorption capacity of activated carbon derived from meranti wood (Shore spp) for mercury (Hg) removal from liquid waste. To establish the relationship between concentration and absorbance, the method employed involves calibrating mercury concentration using calibration curves. Additionally, the effects of pH and exposure time on adsorption capacity were examined. The results indicate that activated carbon from meranti wood can significantly adsorb mercury, achieving an efficiency level of 97.610% at pH 3, with adsorption stability reached within 80 minutes at an adsorption rate of 94.30%. The conclusions drawn from this study suggest that activated carbon from meranti wood is a sustainable and effective solution for addressing mercury contamination in wastewater. It also highlights the importance of regulating pH and exposure time. This research contributes significantly to the development of environmentally friendly methods for water purification.